Business Research in Developing Economies: Evidential MBA Theses Approach – Case of Jordan - Ali Faleh Alalawneh, Ammar; Fahed Saleh Alkhatib, Saleh (Jordan Journal of Business Administration, 2023)
This study aims to scholarly analyze the trends in business research and its significance for developing economies. As a case-study approach, the trends and methodological issues in MBA theses during the span from 1996 to 2018 in Jordan have been considered. Further, keeping the broader research theme intact, significant attention has been given to the analysis of operations and information systems. A total of 283 MBA theses have been ascertained and analysed, where both descriptive and in-depth analyses of data have been conducted. The findings exposed a number of critical business-research problems. These problems affect both the applicability and quality of research works and limit their contributions in academic and practical fields. Several conclusions, policy implications and directions for future research have been suggested for academia and practitioners in business